Dynamics of Japanese Transnational Community and Its Impacts on Local Development: A Case Study of Ethnic Communities in Mae Suai District, Chiang Rai Province, Thailand - หัตถผสุ จารุวรรณ (Journal of Roi Et Rajabhat University, 2025)
This study aimed to 1) explore the dynamics of the Japanese transnational community under the Rungarun (dawn) Project in Chiang Rai Province, Thailand, 2) analyze the international and global dimensions of cultural exchange that emerged from the project, and 3) examine the impacts of these dynamics on local development within ethnic communities in Mae Suai District, Chiang Rai Province. A qualitative research methodology was employed, comprising document analysis and ethnographic fieldwork. Data collection included in-depth interviews with 30 Japanese participants and 40 locals, participant and non-participant observations, and focus group discussions. The findings revealed that the Rungarun Project fostered a Japanese transnational community through shared values in education, sustainable agriculture, and the preservation of ethnic cultures. Japanese individuals from both Thailand and abroad participated through on-site involvement, financial support, and community-based activities, forming an expanding transnational network. This network positively impacted local development in ethnic communities. For example, at Ban Lo Jor, women practiced traditional weaving to increase income and preserve cultural heritage. At Ban Pa Kia, sustainable agricultural practices enhanced household income and promoted community cooperation. The study suggested that the formation of modern transnational communities was no longer confined by geographical proximity, but it was shaped by shared values and interests. These communities developed through broad social networks that supported cultural exchange, knowledge sharing, and sustainable local development.